2011
DOI: 10.1371/journal.pone.0017989
|View full text |Cite
|
Sign up to set email alerts
|

Complete Sequencing of pNDM-HK Encoding NDM-1 Carbapenemase from a Multidrug-Resistant Escherichia coli Strain Isolated in Hong Kong

Abstract: BackgroundThe emergence of plasmid-mediated carbapenemases, such as NDM-1 in Enterobacteriaceae is a major public health issue. Since they mediate resistance to virtually all β-lactam antibiotics and there is often co-resistance to other antibiotic classes, the therapeutic options for infections caused by these organisms are very limited.MethodologyWe characterized the first NDM-1 producing E. coli isolate recovered in Hong Kong. The plasmid encoding the metallo-β-lactamase gene was sequenced.Principal Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
159
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(168 citation statements)
references
References 34 publications
7
159
0
2
Order By: Relevance
“…Similarly to what has been described for the msr(D) gene, the msr(E) gene has been concomitantly reported with the mph(E) gene to be part of a common operon in both Gram-positive (Desmolaize et al, 2011b) and Gram-negative microorganisms, including E. coli, Salmonella enterica and C. freundii (Dolejska et al, 2013;Du et al, 2012;Gołebiewski et al, 2007;Gonz alez-Zorn et al, 2005;Ho et al, 2011) of different origins, including livestock. It is of note that the msr(E) gene is frequently referred to as the mel gene, while the mph(E) is indicated as the mph2 gene in most of the studies performed in Gram-negative microorganisms.…”
Section: Transferable Efflux Pumpssupporting
confidence: 55%
See 2 more Smart Citations
“…Similarly to what has been described for the msr(D) gene, the msr(E) gene has been concomitantly reported with the mph(E) gene to be part of a common operon in both Gram-positive (Desmolaize et al, 2011b) and Gram-negative microorganisms, including E. coli, Salmonella enterica and C. freundii (Dolejska et al, 2013;Du et al, 2012;Gołebiewski et al, 2007;Gonz alez-Zorn et al, 2005;Ho et al, 2011) of different origins, including livestock. It is of note that the msr(E) gene is frequently referred to as the mel gene, while the mph(E) is indicated as the mph2 gene in most of the studies performed in Gram-negative microorganisms.…”
Section: Transferable Efflux Pumpssupporting
confidence: 55%
“…In this context, the acquisition and maintenance of a TMMR may be enhanced in an environment with a high presence of macrolides due to competitive advantages. Besides, indirect selection may also be made, because some TMMR are present in genetic structures that also include other antibiotic resistance determinants such as dfrA genes, involved in resistance to trimethoprim, aacA or aadA genes, involved in aminoglycoside resistance or b-lactamase genes, involved in b-lactam resistance, among others (Dolejska et al, 2013;Du et al, 2012;Ho et al, 2011;Pons et al, 2015;S aenz et al, 2010). Thus, the TMMR may be fixed in the bacterial genetic background by the use of unrelated antimicrobial agents, or by the presence of heavy metals or antibiotic traces in the environment as has been described in other cases (Stepanauskas et al, 2006;Vien et al, 2012).…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The DNA sequence analysis showed that there was a class 1 integron cassette array (intI1-dfrA12-orfF-aadA2-qacED1-sul1) and an insertion sequence ISCR1 on the downstream side of the rmtB gene in plasmid pEC008. Upstream of the rmtB gene, the structure bla TEM-1 -ISCfr1-aacC2-IS26 was found, which has also been reported in the IncL/M plasmid pCTX-M3, pNDM-HK and pEI1573, isolated from Citrobacter freundii, E. coli and Enterobacter cloacae, respectively (Gołebiewski et al, 2007;Ho et al, 2011;Partridge et al, 2012) (Fig. 1).…”
Section: Genetic Environment Of the Rmtb Genesupporting
confidence: 65%
“…In 2010, a study to investigate the resistance mechanism of 49 Enterobacteriaceae isolates with decreased susceptibility to carbapenems collected at 16 teaching hospitals in China,confirmed the production of KPC-2, IMP-4 and IMP-8 carbapenemase 17 . In 2011, the first NDM-1 producing E. coli isolate was detected in Hong Kong 18 .Here we report the emergence of Enterobacteriaceae harboring IMP-4 or IMP-8 carbapenemases in a Chinese tertiary care hospital. This report describes the emergence, the infection control measures implemented, and the results of molecular investigations.…”
Section: Introductionmentioning
confidence: 84%